Epidemiologic Associations Vary Between Tetracycline and Fluoroquinolone Resistant Campylobacter jejuni Infections - Rodrigues, Jose A.; Cha, Wonhee; Mosci, Rebekah E.; Mukherjee, Sanjana; Newton, Duane W.; Lephart, Paul; Salimnia, Hossein; Khalife, Walid; Rudrik, James T.; Manning, Shannon D. (Frontiers in Public Health, 2021)
Campylobacter jejuni is the leading cause of bacterial gastroenteritis and antibiotic resistant C. jejuni are a serious threat to public health. Herein, we sought to evaluate trends in C. jejuni infections, quantify resistance frequencies, and identify epidemiological factors associated with infection. C. jejuni isolates (n=214) were collected from patients via an active surveillance system at four metropolitan hospitals in Michigan between 2011 and 2014. The minimum inhibitory concentration for nine antibiotics was determined using microbroth dilution, while demographic and clinical data were used for the univariate and multivariate analyses. Over the four-year period, a significant increase in the recovery of C. jejuni was observed (p≤0.0001). Differences in infection rates were observed by hospital and several factors were linked to more severe disease. Patients residing in urban areas, for instance, were significantly more likely to be hospitalized than rural residents as were patients over 40 years of age and those self-identifying as non-White, highlighting potential disparities in disease outcomes. Among the 214 C. jejuni isolates, 135 (63.1%) were resistant to at least one antibiotic. Resistance was observed for all nine antibiotics tested yielding 11 distinct resistance phenotypes. Tetracycline resistance predominated (n=120; 56.1%) followed by resistance to ciprofloxacin (n= 49; 22.9%), which increased from 15.6% in 2011 to 25.0% in 2014. Resistance to two antibiotic classes was observed in 38 (17.8%) isolates, while multidrug resistance, or resistance to three or more classes, was observed in four (1.9%). Notably, patients with ciprofloxacin resistant infections were more likely to report traveling in the past month (Odds Ratio (OR): 3.0; 95% confidence interval (CI): 1.37, 6.68) and international travel (OR: 9.8; 95% CI: 3.69, 26.09). Relative to patients with only tetracycline resistant infections, those with ciprofloxacin resistance were more likely to travel internationally, be hospitalized and have an infection during the fall or summer. Together, these findings show increasing rates of infection and resistance and highlight specific factors that impact both outcomes. Enhancing understanding of factors linked to C. jejuni resistance and more severe infections is critical for disease prevention, particularly since many clinical laboratories have switched to culture-independent tests for the detection of Campylobacter.